Optimal PI controller based PSO optimization for PV inverter using SPWM techniques - Abdolrasol M.G.M.; Hannan M.A.; Hussain S.M.S.; Ustun T.S. (Elsevier Ltd, 2023)
Controllers; Distributed power generation; Electric inverters; Modulation; Two term control systems; Voltage control; Modulation indexes; Optimisations; Proportional integral controllers; PV inverter; PV system; Sinusoidal pulse width modulation techniques; Sinusoidal pulsewidth modulations (SPWM); Three phase; Three phasis; Total harmonic distortions; Particle swarm optimization (PSO)